Vibrational quenching of excitonic splittings in H-bonded molecular dimers: adiabatic description and effective mode approximation - Kopec, Sabine; Köppel, Horst (The journal of chemical physics, 2012)
The quenching of the excitonic splitting in hydrogen-bonded molecular dimers has been explained recently in terms of exciton coupling theory, involving Förster's degenerate perturbation theoretical approach [P. Ottiger, S. Leutwyler, and H. Köppel, J. Chem. Phys. 136, 174308 (2012)]. Here we provide an alternative explanation based on the properties of the adiabatic potential energy surfaces. In the proper limit, the lower of these surfaces exhibits a double-minimum shape, with an asymmetric distortion that destroys the geometric equivalence of the excitonically coupled monomers. An effective mode is introduced that exactly reproduces the energy gain and amount of distortion that occurs in a multi-dimensional normal coordinate space. This allows to describe the quenched exciton splitting as the energy difference of the two (S1 and S2) vibronic band origins in a one-dimensional (rather than multi-dimensional) vibronic calculation. The agreement with the earlier result (based on Förster theory) is excellent for all five relevant cases studied. A simple rationale for the quenched exciton splitting as nonadiabatic tunneling splitting on the lower double-minimum potential energy surface is given.
Gesehen am 25.10.2018